Comparison of i-gel™ supraglottic device with classic laryngeal mask airway in anesthetized paralyzed children undergoing elective surgery - Das, Bikramjit (Medknow Publications & Media Pvt Ltd, 2012)
CONTEXT: The newest variation of the i-gel supraglottic airway is a pediatric version. AIMS: This study was designed to investigate the usefulness of the size 2 i-gel compared with the classic laryngeal mask airway (cLMA) of the same size in anesthetized, paralyzed children. SETTINGS AND DESIGN: A prospective, randomized, single-blinded study was conducted in tertiary care teaching hospital. SUBJECT AND METHODS: Sixty ASA grade I–II patients undergoing lower abdominal, inguinal, and orthopedic surgery were included in this prospective study. The patients were randomly assigned to i-gel and cLMA groups (30 patients in each group). Size 2 supraglottic airway was inserted according to the assigned group. We assessed ease of insertion, hemodynamic data, oropharyngeal sealing pressure, and postoperative complications. STATISTICAL ANALYSIS USED: Parametric data were analyzed with the unpaired t-test and non-parametric data were analyzed with the Chi-square test. Unless otherwise stated, data are presented as mean (SD). Significance was taken as P < 0.05. RESULTS: There were no differences in the demographic and hemodynamic data among the two groups. The airway leak pressure of the i-gel group (26.1 ± 2.4 cm H(2)O) was significantly higher than that of the cLMA group (22.64 ± 2.2 cm H(2)O). The success rates for first attempt of insertion were similar among the two devices. There were no differences in the incidence of postoperative airway morbidity among the two groups. CONCLUSIONS: Hemodynamic parameters, ease of insertion, and postoperative complications were comparable between the i-gel and cLMA groups, but airway sealing pressure was significantly higher in i-gel group.